1990
DOI: 10.1128/mcb.10.3.1192-1198.1990
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Foreign Gene in a Line of Transgenic Mice Is Modulated by a Chromosomal Position Effect

Abstract: Unusual aberrant expression of a foreign gene in a particular transgenic mouse line is often attributed to chromosomal position effect, although proof of this is lacking. An alternative explanation is that expression has been modified by the arrangement of multiple copies of the foreign gene at the insertion site or by mutation or gene rearrangement. We have distinguished between these explanations in the case of one particular transgenic line by recovering the aberrantly expressed foreign DNA and reintroducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This squares with evidence that nickel compounds are carcinogenic yet show no mutagenicity in mammalian cell assays. It is well established that chromosomally integrated transgenes in transfected cell lines and transgenic animals are susceptible to inactivation by changes in chromatin structure, thus revealing that chromatin structural change is a potential mechanism of transcriptional regulation .…”
mentioning
confidence: 99%
“…This squares with evidence that nickel compounds are carcinogenic yet show no mutagenicity in mammalian cell assays. It is well established that chromosomally integrated transgenes in transfected cell lines and transgenic animals are susceptible to inactivation by changes in chromatin structure, thus revealing that chromatin structural change is a potential mechanism of transcriptional regulation .…”
mentioning
confidence: 99%
“…Quantitative analysis of integrated green fluorescent protein ( Gfp ) genes showed that integrated copies of the transgene were highest in the 13-line ( Figure 1 B). However, the amount of integrated transgene is not proportional to its expression level because the exogenous transgene is affected by the site of chromosomal integration [ 25 , 26 ]. Therefore, we analyzed the expression of Npgl mRNA in the mediobasal hypothalamus (MBH).…”
Section: Resultsmentioning
confidence: 99%
“…BS6-tk-supF (TR) contains two copies of BS6-tk-supF, each lacking a short 5' region and separated by a 500-bp fragment of mouse DNA, which were integrated at a single chromosomal site in a line of transgenic mice (2, 27a). The complete tandem dimer together with flanking DNA sequences was recovered from two bacteriophage lambda clones and reintroduced into the mouse genome (2). These constructs displayed different patterns of tissue-specific expression (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…2A and C, lane 1) and must therefore be a reverse transcript, possibly related to a reverse transcript previously observed in cells infected with HSV-1 (18, 25). Line L78 carries a full-length copy and a second truncated copy of the 5' end of the BS6-tk-supF gene (2). L78 uniquely has a third short (500-bp) testis transcript (Fig.…”
Section: Resultsmentioning
confidence: 99%